Liberdade de expressão: uma reflexão sobre os seus limites na experiência brasileira - Salvador, Carla Cristina (Universidade do Vale do Rio dos Sinos, 2021)
Freedom of Expression is a fundamental right of utmost importance and indispensable for the caracterization and preservation of the democratic regime. Since the 17th century, several thinkers had already highlighted the importance of freedom of expression and devoted efforts to delineate its fundamentals and reach. Despite the advance and consolidation of the right to freedom of expression, we have been daily confronted with the characteristics of an intolerant Society opposed to divergent ideas. In this context, the general objective of this work is to discuss about the limits of the right to freedom of expression, using exploratory, empirical and bibliographic research methods. Therefore, the path to be taken runs through the establishment of the bond between tolerance and freedom of expression, as well as recapture the arguments of the legal-philosophical teories that support this right. Posteriorly, it shows the path taken by freedom of expression in Brazilian Constitutions until its consolidation as a fundamental right on The Federal Constitution of 1988. Thenceforward, transcending the initial stage of supporting the importance of the right to freedom of expression, the present work begins to address its limits, both the limits established by the Constitution itself, and those defined by the Supreme Federal Court‘s jurisprudence. Lastly, it approaches the Cancel Culture as a new limit to the right to freely express oneself. All of this will lead, in the end, to the verification that there is a constant tension in the exercise of the right to freedom of expression in spaces that guarantee the pluralism of world perspectives, since, on the one hand, if it seeks to enhance the broadest freedom of expression, in its various forms and dimensions, on the other hand, it is also intended to blame those who abuse its exercise.
Keywords: Liberdade de expressão; Direitos fundamentais; Limites; Cultura do cancelamento; Freedom of expression; Fundamental rights; Limits; Cancel culture; ACCNPQ::Ciências Sociais Aplicadas::Direito